Index of glucose effectiveness derived from oral glucose tolerance test - Nagasaka, Shoichiro; Kusaka, Ikuyo; Yamashita, Koh; Funase, Yoshiko; Yamauchi, Keishi; Katakura, Masafumi; Ishibashi, Shun; Aizawa, Toru (Acta diabetologica, 2012)
Aim of this study was to formulate an index for glucose effectiveness (Sg), SgIo, based on 3-point (0, 30 and 120 min) 75 g oral glucose tolerance test (OGTT). The equation for SgI O was developed in the Chikuma cohort ( n = 502). Firstly, post-loading plasma glucose without insulin action and Sg (PPG-without insulin and Sg) was calculated as follows: fasting plasma glucose (mg/dl) + [0.75 × 75,000]/[0.19 × BW(kg) × 10]. Secondly, ‘PPG-without insulin/with Sg’ was obtained from inverse correlation between log 10 DI O and 2-h post-glucose plasma glucose at OGTT (2hPG) in each glucose tolerance category: DI O denotes oral disposition index, a product of the Matsuda Index and δIRI 0–30 /δPG 0–30 . Thirdly, expected 2hPG (2hPG E ) of a given subject was obtained from the regression, and the ratio of 2hPG to 2hPG E (2hPG/2hPG E ) was determined as an adjustment factor. Lastly, SgI O ([mg/dl]/min) was calculated as . SgI O was validated against Sg obtained by frequently sampled intravenous glucose tolerance test in the Jichi cohort ( n = 205). Also, the accuracy of prediction of Sg by SgIo was tested by the Bland–Altman plot. SgI O was 3.61 ± 0.73, 3.17 ± 0.74 and 2.15 ± 0.60 in subjects with normal glucose tolerance (NGT), non-diabetic hyperglycemia and diabetes, respectively, in the Chikuma cohort. In the Jichi cohort, SgI O was significantly correlated with Sg in the entire group ( r = 0.322, P < 0.001) and in subjects with NGT ( r = 0.286, P < 0.001), and SgIo accurately predicted Sg. In conclusion, SgI O could be a simple, quantitative index for Sg.